Strategies to realise the decoloniality of the Comparative and International Education curriculum in South African higher education - Maluleka, K. J. (South African Journal of Higher Education, 2023)
This article sought to investigate the implementation of strategies to realise the decoloniality of the Comparative and International Education (CIE) curriculum in South African higher education. This is a qualitative study in which the participants were selected from CIE senior lecturers and students who are registered for the CIE module. Data was collected from four senior lecturers and nine students who were identified using multi-stage sampling. Data pertaining to the experiences of these academics and students were collected by semi-structured interviews. The study revealed numerous decolonial challenges, including people valuing the Western system more than their own system and a reluctance to move out of their comfort zone. Valuable information was received from the participants suggesting strategies to realise the decoloniality of the CIE curriculum in South African higher education. Based on the suggestions made by participants, this study recommends ways in which to implement strategies of the decoloniality of the CIE curriculum.